Interest Rates and Interest Rate Risk - Jasienė, Meilė (Ekonomika, 2002)
Investigation of interest rates and their factors can be divided in general into two groups according Liquidity preference theory or Loanable funds theory. A very traditional determination of interest rates is explanation as the price at which loanable funds’ supply and demand is in equilibrium. Interest rates play an important role in distribution of loanable funds between sources and users. Interest rate risk is the risk related to unexpected changes in interest rates that may raise or lower net interest income, net interest margin, and market value of stockholders’ equity. Asset / liability and interest rate risk management is a fluid process. The dynamics of the balance sheet and frequently changing market interest rates force it to be continuous activity. Banks can take two basic approaches to reduce exposure to interest rate risk: to hedge interest rate risk: to hedge interest rate risk or to accurately forecast interest rate movements. There is the large number of serious forecasters and wide variety of forecasting methods and models, however, published publicly interest rates’ forecasts are Dot reliable. The ultimate responsibility for the establishment of interest rate risk management policy lies with the Bank’s Board. The specific responsibilities of administering the policy usually are delegated to the Asset / Liability Management Committee (ALCO). ALCO is responsible for formulation, revision, and administration of the interest rate risk management policy and strategies. Development of an interest rate risk management process includes the development of information and monitoring system and formulation of appropriate strategies and tactics. Most banks use either a GAP model, duration model, o their combination. As Lithuanian banks’ interest rate analysis shows, we have had decreasing interest rates and net interest margin during last years. However, the net interest margin is much higher in large banks than in small banks. It confirms in indirect way better skills and possibilities for managing interest rate risk in large banks.